LIPID PROFILE AND PLATELET AGGREGATION OF ETHANOLIC SEED EXTRACT OF AVOCADO (PERSEA AMERICANA MILL.) IN HYPERLIPIDEMIC MALE WISTAR RAT - Soemardji, Andreanus Andaja; Umar, Matuar Hi; Fidrianny, Irda (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this research was to investigate the effect of ethanol seed extract of avocado (ESEA) (Persea americana Mill.) on lipid profile and platelet aggregation in hyperlipidemic male Wistar rat. Methods: The avocado seed was extracted using 70% ethanol by the reflux method. The induction method was conducted by giving high cholesterol intake and oral administration of pure cholesterol, cholic acid, and propylthiouracil. Antiplatelet aggregation parameters were measured by observing of bleeding time (BT), coagulation time (CT), and antiplatelet aggregation activity using adenosine 5'-diphosphate (ADP) as aggregation inductor. Lipid profile such as total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL), as well as the parameters of platelet aggregation were measured before the induction, the end of induction and the end of therapy. Results: ESEA 10 mg/kg bw showed decreasing in TC and LDL levels which was significantly different compare to control group (p<0.05) while ESEA 20 and 40 mg/kg bw gave decreasing in TG. All of doses of extract showed no increasing in HDL levels. In antiplatelet aggregation effect test, ESEA 10 mg/kg bw had the ability to extend BT. ESEA 20 and 40 mg/kg bw had the ability to extend the CT. All of doses of extract showed significantly different (p<0.05) on the measurement of aggregation activity by decreasing in plasma absorbance. Conclusion: The result suggested lipid lowering and anti-aggregation potential of ESEA, which serves as a new potential herbal product and good for cardiovascular disease treatment because it can reduce both risk factors causing the disease. Keywords: Cholesterol, Platelet aggregation, Avocado, Persea americana Mill., Seed.